The allocation of fire stations using set cover approaches - Nik Lah, Nik Fatihah; Abd Rahman, Rosshairy (Universiti Tun Hussein Onn Malaysia, 2018)
Fireman is one of the most significant job in our country with multiple important task especially during fire and accident. Thus, the allocation of sufficient fire station is vital to cover the whole community within specific time. Consequently, this paper aims to build a framework to determine the specific number of fire station to be allocated in order to serve the whole community in Changlun Town, Kedah using set cover approaches. This approach is regularly employ in allocating the minimum number of fire station to cover the specific area with specific time limit. This study uses one of the core model in set cover problem which is known as Location Set Cover Problem. This model is designed for determining the specific number of fire station to ensure that all area in Changlun are covered within 15 minutes time. Greedy heuristic is used as a technique to accomplish the objective of this paper and gives out the best solution by proposing a specific location of these fire stations. This solution can be a guidance to government in designing and developing Changlun in the future.